Pengaruh Love Of Money dan Religiusitas terhadap Fraud Accounting Anggaran Dana Desa pada Kecamatan Sinjai Tengah - Muhaimin Muhaimin (YUME : Journal of Management, 2021)
This study aims to determine the village expenditure budget. This type of research is descriptive quantitative research. The population in this study were employees of the village office of the Central Sinjai District. The number of samples in this study were 33 respondents. Sampling was done using purposive sampling method, the sampling technique was purposely determined according to the research needs. The aim is to obtain samples in accordance with the requirements and objectives of the study so as to obtain accurate data. The results of the data analysis research are multiple regression which shows that love of money has a positive effect and religiosity has a negative effect on fraud accounting. The R Square value of 0.157 means 157% and based on the t-table test value of 1.69552. Keywords: Love of money, religiosity, fraud accounting